Prepregnancy Genetic Carrier Screening in Recipients of Hematopoietic Stem Cell Transplants. Issue 4 (October 2019) - Aluko, Ashley; Seidler, Emily; Penzias, Alan
Abstract : BACKGROUND: Genetic carrier screening of individuals with a history of hematopoietic stem cell (HSC) transplant is not always straightforward. CASE: We present the case of a couple who underwent prepregnancy genetic screening before fertility treatment. The genetics laboratory flagged the male partner's blood sample because there was a discrepancy between the sex of the patient and the sex chromosome markers, ultimately leading to the discovery of a prior HSC transplant. CONCLUSION: A history of HSC transplant may confound results of serum-based genetic carrier screening. Hematopoietic stem cell transplant recipients are at risk for misinterpreted genetic carrier screening because the results of such screening may not actually be reflective of their own DNA. Abstract : A history of hematopoietic stem cell transplant may confound results of serum-based prepregnancy and prenatal genetic carrier screening.